Income Inequality between Formal-Informal Employees Based on Education Group - Riska Dwi Wulandari; Susilo Susilo; Dias Satria (Economics and Finance in Indonesia, 2018)
Integrally, the informal sector deals with the formal sector with pro-cyclical nature or as a complementary sector. Such conditions allow for wage disparity between sectors even in the same education group. Thus, this study seeks to determine the determinants of wage inequality between formal and informal employees in skilled and unskilled workers in Indonesia in 2017 using Blinder-Oaxaca decomposition. The results showed that the discrimination factor had a greater influence than the endowment factor on wage inequality and the endowment factors that contributed to the increase in wage inequality between the two groups were age squared, experience, and job training.